Erratum: Correction: The role of stickiness in the rheology of semiflexible polymers (Soft matter (2019) 15 24 (4865-4872)) - Golde, Tom; Glaser, Martin; Tutmarc, Cary; Elbalasy, Iman; Huster, Constantin; Busteros, Gaizka; Smith, David M.; Herrmann, Harald; Käs, Josef A.; Schnauß, Jörg (Soft Matter, 2019)
Correction for 'The role of stickiness in the rheology of semiflexible polymers' by Tom Golde et al., Soft Matter, 2019, 15, 4865-4872.
CRIS-Team Scopus Importer:2019-10-25